Interactions of Cryoprotectants with Liposomes from Total Lipids of the Fowl Spermatozoa - Linnik, T. P.; Dyubko, T. S.; Martynyuk, I. N.; Tereschenko, A. V. (Problems of Cryobiology and Cryomedicine, 2010)
Using the fluorescent probe FME we studied interactions of the cryoprotectants: ethylene glycol (EG), 1,2-propane diol (1,2-PD), N,N-dimethyl formamide (DMFA), N,N-dimethyl acetamide (DMAc), glycerol and dimethyl sulfoxide (DMSO) with liposomes made from the fowl spermatozoa total lipid (FSTL). It was established that the level of CP impacts on bilayer is determined by hydrophilic-hydrophobic balance of their molecules and showed a concentration dependence. The cryoprotectants are ranked by their increasing influence on FME fluorescence spectral parameters in RSTL liposomes as follows: glycerol â‰¤ EG < 1,2-PD < DMSO < DMAc â‰¤ DMFA, that corresponds the growth in their distribution coefficients in the system â€œwater â€“ non-polar phaseâ€. A mechanism of the cryoprotectant impacts on bonds forming bilayer is discussed.